The power of dependence : NATO-UN cooperation in crisis management - Harsch, Michael F. (Oxford : Oxford University Press, 2015)
A lack of inter-organisational cooperation often results in contradictory policies and can have severe consequences for civilians and international personnel in conflict regions. Scholars often overlook inter-organisational cooperation or provide only partial explanations for its logic and variation. This book puts forward an innovative resource dependence approach to explain the stark variation in cooperation, combining insights from international relations theory and organisational science into a comprehensive theoretical framework.
Includes bibliographical references and index.
Description based on print version record.
Keywords: North Atlantic Treaty Organization; United Nations. -- General Assembly; Crisis management; Kosovo War, 1998-1999.; Afghan War, 2001-; Bosnia and Hercegovina -- History -- 1992-